Household food insecurity and children dietary diversity during the COVID-19 outbreak - Suryana Suryana; Lalu Juntra Utama; Yulia Fitri; Andi Eka Yunianto; Rian Diana; Bustami Bustami (AcTion: Aceh Nutrition Journal, 2023)
The COVID-19 pandemic raises the likelihood of food insecurity and affects the nutritional status of children. This study aims to examine the relationship between household food poverty and children's dietary diversity. The cross-sectional study has done at Lhokseumawe City and North Aceh District. A sample of 289 children aged 12–59 months participated in this study. The Food Insecurity Experience Scale (FIES) was used to measure household food insecurity. Meanwhile, the Individual Dietary Diversity Score (IDDS) was done to assess children's dietary diversity. The Chi-square was employed to analyze the association between household food insecurity and children's dietary diversity. The prevalence of household food insecurity was 8,3%, consisting of 5,5% moderate food insecurity and 2,8% severe food insecurity. Most children had diverse food consumption (88,6%). However, 11,4% of children had low dietary diversity. Household food insecurity was significantly correlated with children's dietary diversity (p= 0,002). Conclusion, the COVID-19 pandemic indirectly impacts household food insecurity, which can worsen the condition of food consumption for toddlers, especially regarding diversity in food consumption. A strategy is required to assist food-insecure households to maintain and increase children's dietary diversity.